Client protection and sustainability of Islamic microfinance institution: evidence from Amanah Ikhtiar Malaysia / Nor Maisarah Bakar - Bakar, Nor Maisarah (2016)
Islamic microfinance Institutions (IMFIs) provide credit to poor recipients, enabling them to gain access to financial assistance, while at the same time having their rights protected. To ensure that clients are protected, all IMFIs should adhere to basic corporate governance principles in ensuring uniform standards, transparency and good corporate governance practices in their institutions. This study explores on the client protection practices and sustainability of Amanah Ikhtiar Malaysia (AIM). The main objective of this study is to examine if client protection affects the sustainability of AIM. The main source of information is the questionnaire survey that has been conducted by taking AIM staff as respondents. Finding shows that the level of client protection in AIM is high. It shows that AIM has high awareness regarding client protection issue. Further analysis shows that accountability and debt collection process have significantly influence the level of sustainability of AIM whereas transparency and transaction costs have insignificantly impact the level of sustainability of AIM. This result implies that having better debt collection process policy and accountability will enhance the level of sustainability of AIM. This study has exclusively contributed to the industry of Islamic microfinance which it gives focuses on client protection issues, which is lacking in Malaysia. This also can be practiced by other IMFIs to ensure that they can sustain in the market for foreseeable future.